Vibration and position control of a flexible manipulator - Mahmood, Iskandar Al-Thani; Bhikkaji, Bharath; Moheimani, S.O. Reza (2007)
A single-link flexible manipulator is fabricated. This flexible manipulator is modeled as a SIMO system with the motor-torque as the input and the hub angle and the tip position as the outputs. The two transfer functions are identified using frequency-domain system identification. A polynomial based feedback controller is designed to damp hub angle response. This controller also damps the tip position response. Apart from damping the system, the feedback controller also provides substantial robustness. Finally, an integral controller is also designed to achieve zero-steady state error in the tip position.